¡Vamos! : Let's go read - Raúl the Third, 1976- (Raúl the Third, 1976- World of ¡vamos!, 2023)
"Little Lobo and his friends are excited for the out-of-this-world book festival the Guadalupian Library hosts every year! Everyone has a special book they're looking for, but there's so much to see and do first. From cookbook demonstrations and comics workshops to mask making and language classes, this library has something for everyone. Can Little Lobo, Bernabé, Kooky Dooky, Coco Rocho, and La Chida each find the book of their dreams?"--